Aplication of videothoracoscopy in trauma - experience of a service - Melo,Bruno Vaz de (2015)
Objective: To evaluate patients with chest trauma submitted to videothoracoscopy during hospitalization. In 2007, the Trauma Surgery Group was created in the General Surgery Department of the Hospital Municipal Lourenço Jorge of Rio de Janeiro-RJ, and started following all trauma victims who were admitted to the Hospital. Methods : We conducted a retrospective analysis of patients submitted to thoracoscopy from July 2007 to May 2015, based on a database started at the beginning of this period and on data collection from patients who underwent thoracoscopy. We evaluated the following parameters: procedure effectiveness, indication of the procedure, conversion rate, complications and mortality. We included patients who presented post-traumatic pleural collections, such as retained hemothorax and pleural empyema, and penetrating injury in the thoracoabdominal transition. All patients were hemodynamic stable and signed an informed consent. Results: In the analyzed period 53 patients were submitted to videothoracoscopy; 24 had penetrating trauma (45.3%) and 29, blunt (54.7%), with a predominance of males (75.5%). The procedure was performed in 26 cases of retained hemothorax (49%), 14 cases of empyema (26.5%) and in 13 patients for evaluation of injury in the thoracoabdominal transition (24.5%). The thoracoscopy was effective in resolution of 36 cases (80%), without need for further procedure. There was a conversion rate of 15.5% and 3 procedure complications related (6.6%). Mortality was nil. Conclusion: In this series, videothoracoscopy proved that this diagnostic and therapeutic procedure is safe and effective, if performed by a surgeon with appropriate training, especially when it is indicated in cases of retained hemothorax and evaluation of penetrating thoracoabdominal trauma.